Pengembangan Usaha Weng Coffee Menggunakan Asset Based Community Development - Vely Vely; Sabinus Beni (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Trade also helps improve the regional economy, in this case Bengkayang district, because of Bengkayang's geographical location which is near the border area between Indonesia and Malaysia. Based on this geographical location, culinary businesses can be an option for entrepreneurs/investors. The purpose of this research is to find out the asset-based development strategy that can be carried out by Weng Coffee, to find out how the process of implementing and evaluating the asset-based development strategy carried out by Weng Coffee is. This research uses qualitative research methods using techniques and the type of research used is action research using the Asset Based Community Development (ABCD) approach. Action research is a methodology that is closely related to participant involvement, so that the process and results are greatly influenced by the values and culture of the participants. The results of the research conducted at Weng Coffee were the researcher's desire to open his own business. Several assets owned by Weng Coffee, such as human/individual assets (human capital), environmental assets (natural capital), financial assets (financial capital), social assets (social capital), physical assets (phsycal capital).